Laminar mixed convection flow from a vertical surface with induced magnetic field and convective boundary - Chaudhari, Kamini K.; Sharma, Anil; Jha, Abhay Kumar (Zielona Góra: Uniwersytet Zielonogórski)
The objective of this investigation is to study the influence of thermal radiation and radiation absorption parameter on a mixed convection flow over a continuously moving porous vertical plate under the action of transverse applied magnetic field taking into account the induced magnetic field with convective boundary.
Keywords: thermal radiation; radiation absorption; convective boundary; induced magnetic field